A novel laccase from newly isolated Cotylidia pannosa and its application in decolorization of synthetic dyes. Issue 4 (October 2015) - Sharma, Deepika; Goel, Gunjan; Sud, Amit; Chauhan, Rajinder Singh
Abstract: The present study reports an extracellular laccase from Cotylidia pannosa sequestered from North Western Himalayas, grown in submerged culture and used to investigate its ability to decolorize synthetic dyes. The laccase production was optimized in yeast extract peptone (YEP) broth supplemented with 2% wheat bran at an inoculum level of 2.9x10 8 fungal spores/mL for different parameters like temperature, pH, incubation time and agitation rate. The maximum activity of laccase (10 U/mL) was obtained with wheat bran as the substrate at pH of 5.0 when incubated at 30 °C for 72 h at 120 rpm. The partial characterization revealed a laccase with a molecular mass of 43 kDa and a K m and V max of 3.5 mg/mL and 88.6 U/mL, respectively. The crude enzyme was found to perform optimally at a temperature of 50 °C and a pH of 5.0. The fungus as well as the crude laccase preparation decolourized the synthetic dyes such as congo red, bromophenol blue and coomassie brilliant blue R-250 to different extent. A decolorization efficiency of 94% by fungal biomass and 40% by crude laccase was observed for congo red. The decolorization of synthetic dyes by the novel laccase from C. pannosa makes it an ideal candidate for the treatment of wastewater from industrial effluents.